Outdoor activities: basics and benefits - VUKIĆ, Željko; OPREAN, Alexandru (Presa Universitară Clujeană, 2024)
In a society where traditional classroom settings often dominate the learning landscape, outdoor education provides a breath of fresh air by taking students beyond four walls and immersing them in the natural environment. This educational approach embraces the great outdoors as a dynamic and interactive classroom, offering a wide array of benefits and learning opportunities for students of all ages. . Outdoor education goes beyond simply teaching subjects in an outdoor setting. It is a holistic approach that aims to foster personal, social, and environmental growth through experiential learning. By engaging in a variety of outdoor activities, students develop a deeper connection with nature, gain practical skills, enhance their problem-solving abilities, and build resilience in the face of challenges.